A model HIV/AIDS risk reduction programme in the Philippines : a comprehensive community-based approach through participatory action research - Morisky, Donald E; Ang, Alfonso; Coly, Astou; Tiglao, Teodora V
A 3-year, longitudinal, quasi-experimental study using participatory action research (PAR) was conducted to determine the feasibility and efficiency of an expanded sexually transmitted infection (STI) HIV/AIDS prevention program among diverse high-risk male heterosexual populations in the southern Philippines. A total of 3389 participants ( approximately 200 males from each of 18 study groups) were recruited, and 221 were trained as peer counselors to develop educational materials and reinforce safe sexual practices among their peers. Condom usage (36.10% to 38.70% to 46.31%), attitudes towards condoms (21.67% to 24.55% to 25.15%) and knowledge about HIV/STI transmission (41.87% to 42.19% to 33.31%) increased significantly from baseline to post-test and 6-month follow up, respectively (p < 0.01). Furthermore, the reported STI incidence decreased significantly (7.4% to 4.6% to 2.4%, respectively). Changes differed significantly between the intervention and control group at post-test and follow up (p < 0.01). These findings illustrate the appropriateness of using PAR methodology in promoting and sustaining positive behavior change.
In: Health Promotion International, 2004 vol.19 (1) pages 69-76.
Keywords: Acquired Immunodeficiency Syndrome -- prevention and control; Community Participation -- methods; Condoms -- statistics and numerical data; HIV Infections -- prevention and control; Health Knowledge, Attitudes, Practice; Risk Reduction Behavior; Safe Sex